Modulatory effects of housing conditions on energy related metabolites and insulin in pigs divergently selected for residual feed intake - Le Floc'h, N.; Campos, P. H. R. F.; Fraga, A. Z. [UNESP]; Louveau, I; Chizzotti, M. L. (Wageningen Acad Publ, 2019)
The ability of pigs to cope with a health challenge may depend on their ability to adapt their metabolism. The purpose of this study was to assess the impact of housing conditions on postprandial energy metabolism in growing pigs from two lines divergently selected for residual feed intake (RFI). The trial was based on a 2x2 factorial design (n=6/group) including low-RFI (LRFI) and high-RFI (HRFI) pigs housed in two contrasted hygiene conditions (Clean vs Dirty). After a 6-week challenge period, blood samples were collected during a 4-hour period after a test meal to measure insulin and energy related metabolites. Housing conditions did not affect average concentrations of insulin and energy related metabolites. Average plasma concentrations of insulin were greater and that of triglycerides were lower in LRFI than in HRFI pigs whatever the housing conditions. For these two variables and glucose, the two lines exhibited significant differences in postprandial profiles. Whether this may be related to a different partitioning of energy related nutrients deserves further investigations.
Keywords: pig; inflammation; feed efficiency; energy metabolism